The Effect of Social Media Content Exposure on the Health Literacy of Followers @halodoc - Devi Mulyanti; Muhammad Al Assad Rohimakumullah (Jurnal Indonesia Sosial Teknologi, 2024)
Currently, content about health is an interesting thing on social media Instagram and TikTok, because in addition to being entertaining it is also an information. Halodoc Instagram plays an active role in routinely communicating health information to its users, with content divided into four pillars, namely product knowledge, tips and tricks, health facts, and inspirations. TikTok Halodoc also actively provides content about health involving general practitioners and specialists. The content exposure provided by the @halodoc social media account is very attached to health information, so that it can encourage people, especially its followers, to carry out health literacy activities easily. Health literacy is done by accessing and reading so as to increase knowledge about health. This study examines the effect of exposure to social media content on the health literacy of @halodoc followers. The purpose of this study was to determine how much influence social media content exposure has on the health literacy of @halodoc followers. The method used in this research is quantitative method using a survey or questionnaire. Sampling using non-probility sampling method with accidental sampling of 100 respondents who are followers or followers of Instagram and TikTok social media @halodoc. Based on the research results on the normality test, this study is normally distributed. In the partial hypothesis test (t test), this study found a significant effect of exposure to social media content on the health literacy of @halodoc followers with a value of 54.1%. While the remaining 45.9% is influenced by other factors outside this research model.